THERMODYNAMIC MODELING OF THE INFLUENCE OF ISOTHERMAL DILUTION ON THE TUNGSTEN-BEARING POTENTIAL OF ORE-FORMING FLUID - Shironosova G.P. (My University, 2001)
Proceeding from the concept of the significant role of mixing of abyssal (magmatic) and meteoric fluids in the formation of tungsten ores in granite-related hydrothermal systems, the influence of the dilution of ore-forming fluid on its tungsten-bearing potential was thermodynamically modeled. The calculations were carried out using the GBFLOW program at T = 350°C. The decrease in the concentrations of chlorides and/or fluorides was estimated for the fluid saturated initially with model granite, wolframate mixture, and the sulfide buffer pair FeS + FeS2. The calculations suggest that dilution results in a significant depletion of the solution in W, which correlates with changes in F concentration. Such relationships are consequences of the predominance of HWO3F species. The main reason for W precipitation is the decrease in F concentration in the solution occurring at the expense of fluorite formation and dilution of tungsten-bearing fluid.
Keywords: Tungsten ores; Thermodynamically modeled; GBFLOW program